Study of Policy Formulation in Drafting Regional Regulation Number 3 of 2017 concerning Riau Malay Customary Institutions, Dumai City - Ahmad Tarmizi; Nurfitriana Nurfitriana; Moris Adidi Yogia; Teuku Afrizal; Ari Subowo (Budapest International Research and Critics University, 2021)
This research focuses on the Formulation of Regional Regulation Policy Number 3 of 2017 concerning the Riau Malay Customary Institution, Dumai City. This study aims to examine the process of formulating a Perda policy by the Dumai City DPRD and related institutions. This study used a descriptive qualitative approach, in which the informants were determined by purposive sampling from various related agencies. The results of the study found that the process of determining Perda policies follows the direction of the prevailing laws, but the compilation process has not been carried out in a holistic manner, it is lacking in depth, especially in the phase of setting the policy agenda. In this context, it was found that the identification of the problem was not very deep related to the problems and peculiarities of the local cultural, customary and historical conditions. Apart from the Perda, there is also no clear framework for protecting, defending and fighting for the fate of indigenous peoples and local communities. Furthermore, in the drafting phase, it has not yet mobilized public participation, including providing public space and public discussions. In fact, this shows the openness in the formulation phase of the Perda. The interesting thing here is that the concept of the Perda in broad terms refers too much to the Perda of the Riau Provincial Malay Customary Institution. So it is advisable to clarify the concept and frame work